2014
DOI: 10.1038/ismej.2014.42
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated nitrate enriches microbial functional genes for potential bioremediation of complexly contaminated sediments

Abstract: Nitrate is an important nutrient and electron acceptor for microorganisms, having a key role in nitrogen (N) cycling and electron transfer in anoxic sediments. High-nitrate inputs into sediments could have a significant effect on N cycling and its associated microbial processes. However, few studies have been focused on the effect of nitrate addition on the functional diversity, composition, structure and dynamics of sediment microbial communities in contaminated aquatic ecosystems with persistent organic poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(76 citation statements)
references
References 51 publications
(55 reference statements)
1
65
0
2
Order By: Relevance
“…Betaproteobacteria have a similar variation pattern, though they are often the most abundant bacteria inhabiting the upper waters of lakes (Newton et al., ). Previous studies demonstrated that Proteobacteria are involved in a variety of biogeochemical processes in aquatic ecosystems (Damashek & Francis, ; Xu et al., ; Zhang et al., ). Thus, they are more active due to a greater availability of POC and DOC at that depth, as seen in Figures d and a, which demonstrates that depth has a significant effect on their abundance in freshwater (Gattuso, Peduzzi, Pizay, & Tonolla, ).…”
Section: Resultsmentioning
confidence: 99%
“…Betaproteobacteria have a similar variation pattern, though they are often the most abundant bacteria inhabiting the upper waters of lakes (Newton et al., ). Previous studies demonstrated that Proteobacteria are involved in a variety of biogeochemical processes in aquatic ecosystems (Damashek & Francis, ; Xu et al., ; Zhang et al., ). Thus, they are more active due to a greater availability of POC and DOC at that depth, as seen in Figures d and a, which demonstrates that depth has a significant effect on their abundance in freshwater (Gattuso, Peduzzi, Pizay, & Tonolla, ).…”
Section: Resultsmentioning
confidence: 99%
“…The most drastic change in nitrate treatment occurred in the top layer, in which NH 4 Cl-P increased from 4.08 mg P/ kg on day 1 to 39.9 mg P/kg on day 66. Increase of NH 4 Cl-P in nitrate treatment was likely attributed to the increase of P releasing from decaying cells of bacterial biomass in deposited phytodetrital aggregates as nitrate addition might increase the microbial activity in the sediment (Xu et al 2014).…”
Section: Effects On Phosphorus In the Sedimentmentioning
confidence: 99%
“…Research had shown that nitrate addition could not only eliminate black-odorous and suppress internal phosphorus loading in the contaminated sediment but also successfully stimulate indigenous microorganisms for in situ bioremediation (Hemond and Lin 2010;Xu et al 2014;Yamada et al 2012). Phoslock®, a new lanthanum-modified bentonite, was developed in the 1990s by the Commonwealth Scientific and Industrial Research Organisation (CSIRO) of Australia (Robb et al 2003), and had succeeded in reducing phosphorus in both laboratory and field trials (Meis et al 2012;Meis et al 2013;Lürling and van Oosterhout 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial degradation was one of the most important means to remove PBDEs from contaminated soil [9,26]. In the present study, the PBDE dissipation in the soil planted with A. corniculatum was significantly higher than that in the unplanted soil, and more PBDE dissipation occurred in rhizosphere (R) than non-rhizosphere (non-R) soil (Fig.…”
Section: Effect Of Nitrogen On Microbial Degradation Of Pbdesmentioning
confidence: 69%